RyRCa2+ leak limits cardiac Ca2+ window current overcoming the tonic effect of calmodulinin mice. - María Fernández-Velasco; Gema Ruiz-Hurtado; Angélica Rueda; Patricia Neco; Martha Mercado-Morales; Carmen Delgado; Carlo Napolitano; Silvia G Priori; Sylvain Richard; Ana María Gómez; Jean-Pierre Benitah (PLoS ONE)
Ca(2+) mediates the functional coupling between L-type Ca(2+) channel (LTCC) and sarcoplasmic reticulum (SR) Ca(2+) release channel (ryanodine receptor, RyR), participating in key pathophysiological processes. This crosstalk manifests as the orthograde Ca(2+)-induced Ca(2+)-release (CICR) mechanism triggered by Ca(2+) influx, but also as the retrograde Ca(2+)-dependent inactivation (CDI) of LTCC, which depends on both Ca(2+) permeating through the LTCC itself and on SR Ca(2+) release through the RyR. This latter effect has been suggested to rely on local rather than global Ca(2+) signaling, which might parallel the nanodomain control of CDI carried out through calmodulin (CaM). Analyzing the CICR in catecholaminergic polymorphic ventricular tachycardia (CPVT) mice as a model of RyR-generated Ca(2+) leak, we evidence here that increased occurrence of the discrete local SR Ca(2+) releases through the RyRs (Ca(2+) sparks) cause a depolarizing shift in activation and a hyperpolarizing shift in isochronic inactivation of cardiac LTCC current resulting in the reduction of window current. Both increasing fast [Ca(2+)](i) buffer capacity or depleting SR Ca(2+) store blunted these changes, which could be reproduced in WT cells by RyRCa(2+) leak induced with Ryanodol and CaM inhibition.Our results unveiled a new paradigm for CaM-dependent effect on LTCC gating and further the nanodomain Ca(2+) control of LTCC, emphasizing the importance of spatio-temporal relationships between Ca(2+) signals and CaM function.